New determination of the value of vocational and higher education? : Employees' educational choices, careers and labour market outcomes in Germany - Annen, Silvia [Verfasser]; Tiemann, Michael [Verfasser] (My University, 2021)
"This paper aims to evaluate the adequacy of employees’ job requirements compared to their qualification and to identify typical qualification sequences and career paths in the commercial field. The results aim to contribute to the debate on the relevance of vocational qualifications in the labour market, driven by the trends of academisation in some occupational fields. The analyses are carried out based on the data from the follow-up survey to the BIBB/BAUA Employment Survey of 2018. With regard to qualification-adequate employment, the results show sector-specific differences. Overall, qualification adequacy is higher in the tourism and banking sectors than in trade and logistics. The quantitative analysis of typical training sequences in the four sectors also confirms the important significance of professional career paths in trade and logistics." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.1 Bildungsangebot & -nachfrage; G 1.3.2 Bildungsverhalten und -verläufe; G 1.2.3 Qualifikationsentwicklungen; S 6.4.1 Kaufleute; 370; Bildungsabschluss; Berufliche Qualifikation; Unterqualifikation; Überqualifikation; Berufsverlauf; Qualifikationsverwertung; Akademisierung; kaufmännischer Beruf; Ausbildungsabsolvent; Hochschulabsolvent; BIBB-/BAuA-Erhebung